1996
DOI: 10.1111/j.1528-1157.1996.tb00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Illnesses in Adults with Childhood‐Onset Epilepsy: A Population‐Based 35‐Year Follow‐Up Study

Abstract: Epilepsy per se, but not AEDs, has an apparent association with the occurrence of psychiatric and psychosomatic disorders. Risk for somatic comorbidity is not increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 28 publications
4
61
1
Order By: Relevance
“…Furthermore, the risk of occurrence of psychiatric disorders in adult patients with childhood-onset epilepsy has been recently emphasized. [46] Similarly, the potential adverse effect of repeated seizures on the developing brain, the expectation of some developmental catch up, and the concept of young-brain equipotentiality (plasticity) that allows aggressive surger, have all been important issues in advocating early surgical treatment. [19,20,23,33,73,80] In addition, the recognition of side effects caused by anticonvulsant therapy have positively influenced the trend for alternative management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the risk of occurrence of psychiatric disorders in adult patients with childhood-onset epilepsy has been recently emphasized. [46] Similarly, the potential adverse effect of repeated seizures on the developing brain, the expectation of some developmental catch up, and the concept of young-brain equipotentiality (plasticity) that allows aggressive surger, have all been important issues in advocating early surgical treatment. [19,20,23,33,73,80] In addition, the recognition of side effects caused by anticonvulsant therapy have positively influenced the trend for alternative management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…One population-based case-control study found a 7-fold increased risk for and adult with depression to develop epileptic seizures, ompared to normal individuals. The risk increased to 17-fold with focal epilepsies [49]. Hesdorffer et al [100] observed the same temporal relation between depression and a first seizure, with a 6-fold increased risk.…”
Section: Pshysiopathology Bidirectional Relationmentioning
confidence: 60%
“…Most of these studies involve specific epileptic populations, in tertiary centers for attention to PWE. Community-based epidemiologic studies suggest a lifelong prevalence of psychiatric disorders in PWE, both adults and children, between 20 and 50% [13,[44][45][46][47][48][49][50][51][52]. Recently, Tellez-Zenteno et al [9] using data from the Canadian Community Health Survey, with administration of the World Mental Health Composite International Diagnostic Interview (CIDI), found a lifelong psychiatric disorder diagnosis in 35% of PWE, compared with 20% of non-epileptic individuals.…”
Section: Epidemiologymentioning
confidence: 99%
“…Meanwhile, individuals are exposed to stress factor more at old age than young individuals due to affective problems due to physical challenges, loss of self-confidence, feeling helpless, loneliness, hopelessness, inability to fulfill one's responsibilities, and social challenges such as those due to retirement, loss of productivity and economic difficulties. Jalava et al have demonstrated in their 35-year follow study that patients with epilepsy have a 4-fold increased risk of developing psychiatric disease and are sensitive to stress than normal individuals (28). On the other hand, the relationship between stress and seizures is usually accepted by clinical experience and Nancy et al have demonstrated in the work they have done that stress is a factor that triggers seizures (29).…”
Section: Discussionmentioning
confidence: 99%